2009
DOI: 10.4236/jmmce.2009.84023
|View full text |Cite
|
Sign up to set email alerts
|

Model for Predictive Analysis of the Concentration of Phosphorus Removed during Leaching of Iron Oxide Ore in Sulphuric Acid Solution

Abstract: Model for predictive analysis of the concentration of phosphorus removed (relative to the initial and final pH of the leaching solution) during leaching of iron oxide ore in sulphuric acid solution has been derived. It was observed that the validity of the model is rooted in the mathematical expression; (P/N) 1/3 = (e γ/α ) where both sides of the relationship are almost equal. The model; P = 4.25(e γ/α ) 3 shows that the concentration of phosphorus removed is dependent on the values of the initial and final p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…(11,8) showing densely entangled network. It is a documented fact that obtaining separated SWCNTs during CVD synthesis has not being thermodynamically feasible, due to their high polarization and smooth surface which causes strong van der Waal's interaction (~ 500 eV) and π-π intertube stacking, resulting to formation of large agglomerated bundles and ropes [21][22]. Additionally, the carbide moieties may have polymerized over the sample SWCNTs, as shown in their TEM image of Figure 6, which may also increase the surface tension and therefore the hydrophobicity of the as-grown SWCNTs which resulted in poor dispersion of the sample [7].…”
Section: Analysis Of Swcnt (11 8) Figure 3 X-rd Profile Of Swcntsmentioning
confidence: 99%
“…(11,8) showing densely entangled network. It is a documented fact that obtaining separated SWCNTs during CVD synthesis has not being thermodynamically feasible, due to their high polarization and smooth surface which causes strong van der Waal's interaction (~ 500 eV) and π-π intertube stacking, resulting to formation of large agglomerated bundles and ropes [21][22]. Additionally, the carbide moieties may have polymerized over the sample SWCNTs, as shown in their TEM image of Figure 6, which may also increase the surface tension and therefore the hydrophobicity of the as-grown SWCNTs which resulted in poor dispersion of the sample [7].…”
Section: Analysis Of Swcnt (11 8) Figure 3 X-rd Profile Of Swcntsmentioning
confidence: 99%
“…Studies [3][4][5][6][7][8][9][10] have shown that the phosphorus content of steel products can be reduced during the early stage processing of the iron oxide ore (primary raw material) through hydrometallurgy. This involves leaching out phosphorus (from the ore) and invariably dissolving it in the leaching solution used, which in most cases are acids, while the residue is now dried and used as enhanced concentrate for steelmaking.…”
Section: Introductionmentioning
confidence: 99%
“…Similar acid leaching of iron oxide ore to remove phosphorus, and computational analysis of generated experimental results 10 using a derived model; A process assessment model 11 clearly predicted the quantity of removed phosphorus P, during sulfuric acid leaching of iron oxide ore, based on the combined influence of the initial and final leaching solution pHs on the leaching process ( Table 3) …”
Section: +mentioning
confidence: 99%
“…This formed the basis for several attempts already made to reduce the concentration of phosphorus inherent in iron oxide ores designated for production of engineering materials and orthopedic devices. Successful efforts have been made [8][9][10][11][12] to clearly ascertain the possibility of quantifying the extent of phosphorus removal during processing of iron oxide ore, based on synergistic interaction between some process parameters.…”
Section: +mentioning
confidence: 99%